A stable method for routine analysis of oxylipins from dried blood spots using ultra-high performance liquid chromatography–tandem mass spectrometry. (October 2018) - Hewawasam, Erandi; Liu, Ge; Jeffery, David W.; Muhlhausler, Beverly S.; Gibson, Robert A.
Highlights: A robust method for measuring 21 oxylipins from dried blood spots was developed. Our method affords high–throughput analysis of oxylipins from minimal sample volumes. This method is reproducible and precise enabling the accurate quantitation of oxylipins. Oxylipins were stable for at least 2 months storage at room temperature. This new method is ideal for multi-centre community based studies. Summary: Oxylipins are biologically important lipid mediators that are derived enzymatically from polyunsaturated fatty acids (PUFA) and have a major role in regulating inflammatory processes. The currently available methods for measuring oxylipins from human biological samples have limitations, which restricts their use in large studies. We have developed a novel method for measuring 21 oxylipins from dried blood spot (DBS) using ultra-high performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS) and stable isotope dilution analysis. Our new method is reproducible and precise and enables the high throughput analysis and quantitation of bioactive oxylipins in small volumes of blood. In the future, this new method can be readily applied to measure oxylipins in large studies. Abstract Oxylipins are downstream lipid mediators enzymatically-produced from polyunsaturated fatty acids (PUFA) that are implicated as the biological effectors of these fatty acids. Recently reported methods for the quantitation of oxylipins require complex extraction procedures. In this study, we report the development and validation of a novel system for the quantitation of 21 individual oxylipins from a dried blood spot (DBS) using ultra-high performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) and stable isotope dilution analysis. Linearity and precision of the method were determined and the stabilities of the 12 most abundant oxylipins were tested during 2 months of storage at room temperature, after being spiked into blood and prepared as DBS on PUFAcoat™ paper. Responses were linear across the concentration range analysed for all oxylipins (r 2 values ranged from 0.953 to 0.998). Intra–day and inter–day variations were ≤16% for all oxylipins. Recovery of oxylipins from the DBS ranged from 80 – 115%. The 12 spiked oxylipins were stable for 2 months when stored as DBS at room temperature. Our method is reproducible and precise, and provides the opportunity to accurately quantitate these oxylipins in a small sample volume. Graphical abstract: Image, graphical abstract